Pengelolaan Pendidikan Karakter Bagi Anak Usia Dini dalam Penanaman Nilai-Nilai Kejujuran - Zarrazir, Alifia; Nurussalami, Nurussalami (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Character education plays an important role in shaping a child's personality, especially in instilling the value of honesty which is a major aspect in a child's moral development until they are adults. The success of teachers in instilling the value of honesty in early childhood can be seen through changes in behavior that are reflected in their daily activities. Children who are accustomed to being honest from an early age tend to grow into trustworthy and responsible individuals. TK IT Al-Azhar Cairo Banda Aceh has implemented character education, especially the character of honesty, but there are several factors that influence the process of instilling honesty values ​​in children, both from the teacher's personal side and external factors related to the child's environment. This study aims to determine the planning, implementation and evaluation of children's honesty character in TK IT Al-Azhar Cairo Banda Aceh. This study uses a qualitative method with a descriptive approach. The subjects in this study were the principal, curriculum representative, student representative and teacher. Data were obtained from interviews, observations and documentation. The results of the study indicate that 1. Character education planning at TK IT Al-Azhar Cairo Banda Aceh includes a). determining character education goals that are in accordance with the school's vision and mission, b). preparing rules that support honest behavior, c). integrating honesty values ​​into the curriculum, d). establishing cooperation between schools and parents. 2. The implementation of character education at TK IT Al-Azhar Cairo Banda Aceh, teachers provide real examples through honest attitudes and give appreciation to children who show honesty. 3. Evaluation of character education at TK IT Al-Azhar Cairo Banda Aceh is carried out through direct observation of children's behavior and direct coaching for children as well as recording children's social emotional development in report cards and anecdotal notes.